Photoluminescence, Photoacoustic and Structural Characteristics of Polycrystalline Zn2TiO4: Ni2+ Semiconductor - Gomes,L. P. V. (2020)
This work presents the investigation, at room temperature, of Zn2TiO4samples containing Ni2+ ions as substitutional impurities. Samples with molecular formula Zn2(1-x)Ni2xTiO4, where x = 0.00, 0.0007, 0.001, 0.0013, 0.002 and 0.003, in which Zn2+ ions were replaced by Ni2+ ions, were prepared through solid-state method, crystalline data were obtained by X-ray diffraction, the elemental composition was determined by X-ray fluorescence and the optical properties were investigated through photoluminescence and photoacoustic techniques. The photoluminescence spectra showed broadbands from 640 nm to 800 nm. The emission of the Zn2(1-x)Ni2xTiO4 samples was assigned to the overlapping of the Ni2+and the Zn2TiO4 emission. The most intense photoluminescence signal was obtained with excitation radiation at a wavelength of 360 nm for the sample with x = 0.001. The photoacoustic spectra showed absorption bands characteristic of semiconductor materials due to the host Zn2TiO4. The energy bandgap of the Zn2(1-x)Ni2xTiO4was obtained from photoacoustic absorption spectra.